Anti-reduction high-performance X7R type ceramic material and preparation method thereof

By adding specific additives to BaTiO3 ceramic materials and performing reoxidation treatment, the oxygen vacancy problem during low-oxygen partial pressure sintering is solved, and ceramic materials with high dielectric constant, low loss and high insulation performance are achieved, and temperature stability complies with the X7R standard.

CN119822814APending Publication Date: 2025-04-15UNIV OF ELECTRONICS SCI & TECH OF CHINA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510046523.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-15

Smart Images

  • Figure CN119822814A_ABST
    Figure CN119822814A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-reduction high-performance X7R type ceramic material and a preparation method thereof, belongs to the technical field of electronic materials, and particularly relates to a capacitor material technology. According to the anti-reduction high-performance X7R type ceramic material, superfine ceramic BaTiO3 with the particle size being 180 nm to 230 nm is used as a main material, and a secondary additive comprises MgCO3, SrCO3, Mn3O4 and one or more of rare earth element oxides including Y2O3, Dy2O3, Ho2O3 and Er2O3. The mass ratio of the materials is [100-(a + b + c + d)] BaTiO3 + aMgCO3 + b SrCO3 + c Mn3O4 + d Re2O3. Wherein a, b, c and d are coefficients, and calculated by weight percentage, 0.1 wt% < = a < = 0.9 wt%, 0.1 wt% < = b < = 1.0 wt%, 0.1 wt% < = c < = 0.5 wt%, and 0.1 wt% < = d < = 0.8 wt%. The anti-reduction high-performance X7R type ceramic material disclosed by the invention is prepared by adopting a traditional solid phase method, sintering in a reducing atmosphere and then oxidizing. Through doping modification and process optimization, the reduction resistance, dielectric property and temperature stability of the ceramic material are further improved. The ceramic has the advantages of high dielectric constant (2300-3200), high insulation resistivity (rho is greater than or equal to 1.0 * 10 < 12 > omega.cm), simple preparation process, good repeatability and low price, and is suitable for BME-MLCC.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electronic materials and relates to capacitor material technology. Background Art

[0002] With the rapid development of electronic information technology, the trend of miniaturization, lightweight and high performance of electronic products is becoming increasingly significant. Multilayer ceramic capacitors (MLCC) are widely used in electronic devices due to their small size and high reliability. MLCC is mainly composed of three parts: inner electrode, dielectric layer and terminal electrode. The ceramic dielectric and the metal inner electrode are stacked and sintered, and the terminal electrodes are coated at both ends to prepare MLCC with a monolithic structure. Based on the temperature characteristics of different dielectric materials, MLCC can be divided into Class I and Class II ceramic capacitors. Class I ceramic capacitors (such as C0G materials) have high temperature stability, and the capacitance remains basically unchanged in a wide temperature range. They are often used in compensation circuits and high-frequency circuits. Class II ceramic capacitors have a higher dielectric constant, but relatively poor temperature stability. When the temperature changes, its dielectric constant shows a nonlinear change, which is suitable for applications such as smoothing, coupling and energy storage circuits. According to the standards of the Electronic Industries Association (EIA), the temperature characteristics of Class II ceramic capacitors are further classified, among which the temperature range of X7R ceramic materials is -55°C to 125°C, and the temperature change rate of capacitance (TCC) is less than ±15%, which meets the temperature stability requirements. Therefore, it is widely used in industrial and consumer electronics. According to different metal internal electrodes, MLCC can be divided into base metal internal electrode multilayer ceramic capacitors (BME-MLCC) and precious metal internal electrode ceramic capacitors (PME-MLCC). BME-MLCC often uses relatively cheap metals such as Cu and Ni as internal electrodes, and needs to be sintered in a reducing atmosphere with low oxygen partial pressure. PME-MLCC uses precious metals such as Pb and Ag as internal electrodes. The sintering process is relatively simple and is usually sintered in air.

[0003] Base metal inner electrodes are cheap and have obvious cost advantages, and nickel electrodes have a series of unique advantages, such as low resistivity, low migration rate, and high electrochemical stability. In recent years, with the increasing demand for MLCC, the cost-effective base metal inner electrodes (BME-MLCC) have gradually replaced the precious metal inner electrodes (PME-MLCC). However, in the actual production process, base metal inner electrode MLCC also faces certain technical challenges. Since nickel and copper are easily oxidized when sintered in air, high-temperature sintering is required in a reducing atmosphere to prevent the electrode from oxidizing and losing conductivity. However, when barium titanate-based ceramic materials are sintered in a reducing atmosphere, Ti is prone to occur. 4+ Reduction to Ti 3+At the same time, it will produce freely movable weakly bound electrons and oxygen vacancies, making the ceramic dielectric material n-type semiconductive, resulting in increased dielectric loss and reduced insulation resistance, thus affecting the electrical performance and long-term stability of the capacitor.

[0004] In order to improve the insulation properties of dielectrics and solve the problem of semiconductorization of BaTiO3 ceramics sintered in a low oxygen partial pressure atmosphere, early researchers such as Herbert believed that electrons could be compensated by acceptor doping to reduce the electron concentration. At the same time, pinning with oxygen vacancies inhibits the migration of oxygen vacancies, thereby improving the insulation resistance. Elements such as iron (Fe), cobalt (Co), and manganese (Mn) are easy to enter the Ti site and replace because of their similar ionic radius to titanium (Ti). However, acceptor doping cannot eliminate oxygen vacancies, but may generate new oxygen vacancies. It cannot solve the problem of insulation resistance degradation caused by the generation and migration of oxygen vacancies. Therefore, in practical applications, in order to eliminate the oxygen vacancy defects caused by low oxygen partial pressure, the material needs to be reoxidized in the later stage of sintering to further improve the insulation performance and temperature stability of the material. Later researchers found that rare earth elements with ionic radii between barium (Ba) and titanium (Ti) have "amphoteric effects" and can enter both the A site and the B site of the BaTiO3 perovskite structure, producing donor and acceptor effects at the same time. Compensate for oxygen vacancies and free electrons, and form defect associations to inhibit the migration of oxygen vacancies.

[0005] At present, the countries and regions that have conducted more research on this are Japan, Europe, South Korea, and China. The main domestic research institutions include Tsinghua University, Tianjin University, and University of Electronic Science and Technology of China. Chinese patent application (201811033254.8) discloses a method for improving the reduction resistance of barium titanate dielectric materials by doping with variable valence ions. Based on BaTiO3, a dielectric material with a dielectric constant close to that at room temperature is obtained by adding one or more variable valence ion compounds such as SnO2, MnO2, or NH4VO3. However, its dielectric loss (1.0% to 4.0%) is relatively high, and its insulation resistivity (10 9 Ω·cm) is low. Chinese patent number (202110649477.2) discloses a method for preparing a reduction-resistant X8R type BaTiO3-based ceramic material. By adding Bi2O3, MgO, and ZrO2 to BaTiO3, a dielectric constant of 669 to 2020 and an insulation resistivity of 1.22 to 4.84×10 13Ω·cm and temperature stability that meets EIA X7R and X8R standards. However, its dielectric constant varies widely, and the highest is only 2020. Chinese patent application (202311044107.1) discloses BaTiO3 dielectric ceramics prepared with BaTiO3, Bi2O3, Co2O3 and MnO2 as raw materials. It has good dielectric properties (dielectric constant of 2510~2815) and insulation properties (insulation resistivity of 10 11 ~10 13 Ω·cm), but its temperature stability TCC ≤ ±22% is in the temperature range of -50 to 150°C, which does not meet the widely used EIA X7R and X8R standards.

[0006] At present, it is difficult to take into account the performance of anti-reduction, high capacity, high insulation resistivity, high temperature stability, and low loss in the research of anti-reduction BaTiO3 dielectric ceramics. Therefore, it is necessary to further improve the dielectric constant and insulation resistivity on the basis of anti-reduction, while reducing the sintering temperature of the material and widening the operating temperature range. In order to meet the high specific capacity, low loss and high reliability requirements of future electronic products. Summary of the invention

[0007] The purpose of the present invention is to provide a high-performance X7R type ceramic material which is anti-reduction, highly reliable, low-loss, has a high dielectric constant, complies with the X7R capacitance temperature coefficient variation standard, and is suitable for multilayer ceramic capacitors and a preparation method thereof.

[0008] The technical solution of the present invention is:

[0009] Provided is a high-performance X7R type ceramic material with an anti-reduction property. The dielectric material is mainly made of ultrafine ceramic BaTiO3 with a particle size of 180nm to 230nm, which accounts for 97.40% to 99.10% of the total weight of the dielectric material. Various secondary additives are added, including MgCO3, SrCO3, Mn3O4 and one or more oxides of rare earth elements Y, Dy, Ho and Er, which account for 0.90% to 2.60% of the total weight of the dielectric material, to prepare the high-performance X7R type ceramic material with an anti-reduction property. The mass ratio of the materials is: [100-(a+b+c+d)]BaTiO3+a MgCO3+b SrCO3+c Mn3O4+d Re2O3, where Re2O3 represents the oxide of the rare earth element. The percentage contents of the secondary additives in the total mass of the ceramic material are MgCO3: 0.1-0.9wt%, SrCO3: 0.1-1.0wt%, Mn3O4: 0.1-0.5wt%, and Re2O3: 0.1-0.8wt%.

[0010] The dielectric constant of the above ceramic material is between 2300 and 3200, the dielectric loss is less than 2%, and the capacity temperature change rate is <±15%. It is a type of dielectric ceramic material that meets the X7R standard.

[0011] The method for preparing the ceramic material is characterized by comprising the following steps:

[0012] Step 1: ball-milling and mixing ultrafine BaTiO3 powder with a particle size of 180nm to 230nm and a modified additive composed of one or more of MgCO3, SrCO3, Mn3O4 and rare earth element oxides Y2O3, Dy2O3, Ho2O3, and Er2O3, and then granulating and molding to obtain a green material; wherein the amount of the modified additive added accounts for 0.90% to 2.60% of the total mass of the barium titanate original powder and the additive;

[0013] Step 2: sintering: the green body obtained in step 1 is sintered at 1270°C to 1330°C for 2 to 4 hours in a 1 to 2% H2-N2 mixed reducing atmosphere at a heating rate of 3°C / min and a cooling rate of 4°C / min;

[0014] Step 3: Reoxidation: The sample obtained in step 2 is reoxidized for 2 hours at a temperature of 900°C to 1100°C under the protection of an N2 atmosphere containing O2 to obtain a high-performance X7R ceramic material that is resistant to reduction.

[0015] Furthermore, the ball milling process in step 1 is as follows: deionized water, zirconium balls and powder are mixed in a mass ratio of 2:1:1, and ball milled at a speed of 280 rpm for 3 to 16 hours;

[0016] Furthermore, the granulation process in step 1 is: the ball-milled mixture is dried and mixed with a polyvinyl alcohol aqueous solution and then granulated, and the granulation size is controlled at 80 to 250 meshes;

[0017] Furthermore, the molding process in step 1 is: placing the granulated material into a molding mold and dry pressing it under a pressure of 12 MPa to obtain a green material;

[0018] Furthermore, the reoxidation process in step 3 is as follows: the oxygen content in the N2 atmosphere containing O2 is 10-200 ppm and the gas flow rate is 50-70 sccm.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. The secondary additives in the present invention contain alkaline earth metal elements Mg and Sr, variable valence element Mn, and amphoteric rare earth elements Y, Dy, Ho, and Er with ionic radius between Ba and Ti. Under the joint action of Mg and rare earth elements, it is easier to form a core-shell structure, thereby improving the dielectric temperature stability. Trivalent Mn is reduced in a reducing atmosphere and occupies the B position as an acceptor, which can compensate electrons to a certain extent and protect Ti from being reduced. The defect dipole pair inhibits the migration of oxygen vacancies. The secondary additive SrCO3 forms an excess environment at the A site in BaTiO3 ceramics, and the amphoteric rare earth elements easily enter the B site, generating another defect dipole pair. Under the combined effect of the two defect dipole pairs, the migration of oxygen vacancies is restricted, which greatly improves the anti-reduction performance and reliability of the BaTiO3 ceramic dielectric layer.

[0021] 2. The present invention uses ultrafine ceramic BaTiO3 as the main material, and the doping of some secondary additives causes lattice distortion, which improves the dielectric constant and dielectric temperature stability. The prepared anti-reduction high-performance X7R ceramic material has low dielectric loss (tgδ≤2%) and high insulation resistivity (ρ≥1.0*10 12 Ω·cm), capacitance temperature coefficient that meets X7R standard, higher dielectric constant (2300~3200) and good processability.

[0022] Compared with the prior art, the present invention has the following characteristics:

[0023] 1. In the formula of the present invention, no secondary synthetic additives are required, which is conducive to industrial large-scale production and effectively reduces the complexity of the preparation process.

[0024] 2. In the formula of the present invention, the content of secondary additives is comprehensively regulated to achieve the purpose of synthesizing anti-reduction porcelain by adjusting the stoichiometric ratio and improving the formula, thereby achieving the purpose of comprehensively regulating the dielectric properties.

[0025] 3. In the formula of the present invention, amphoteric rare earth elements and variable valence acceptor elements are co-doped to compensate electrons and inhibit the migration of oxygen vacancies, thereby improving the anti-reduction performance of the barium titanate ceramic dielectric layer and enhancing its temperature stability and insulation properties.

[0026] 4. The present invention optimizes the production process and adopts a two-stage sintering method. After sintering in a reducing atmosphere, reoxidation is performed to reduce the oxygen vacancy concentration and increase the interface barrier, thereby inhibiting the degradation of insulation performance caused by oxygen vacancy migration and improving the reliability of the device. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a schematic flow chart of the method for preparing the anti-reduction high-performance X7R type ceramic material of the present invention.

[0028] Figure 2 It is a characteristic curve diagram of the dielectric constant of the samples of Examples 1-5 of the present invention changing with temperature.

[0029] Figure 3 It is a characteristic curve diagram of the dielectric constant of the samples of Examples 6 to 10 of the present invention changing with temperature.

[0030] Figure 4 It is a curve diagram showing the change of capacitance temperature rate with temperature of samples of Examples 1-5 of the present invention.

[0031] Figure 5 It is a curve diagram showing the change in capacitance temperature rate of samples of Examples 6-10 of the present invention as a function of temperature. DETAILED DESCRIPTION

[0032] Examples 1-10

[0033] Step 1: Ingredients: accurately weigh the ingredients according to the mass ratio of each raw material in Table 1;

[0034] Step 2: ball milling: put the mixed powder into a ball mill, mix deionized water, zirconium balls and powder in a mass ratio of 2:1:1, and ball mill for 10 hours at a speed of 280 rpm;

[0035] Step 3: granulation and molding; the ball-milled powder is placed in an oven at 100°C for drying, 15% by mass of polyvinyl alcohol is added for granulation, the granulation size is controlled at 80 to 250 meshes, and pressed into a green body with a diameter of 1 cm and a thickness of 0.1 cm at 12 MPa;

[0036] Step 4: sintering; the green body obtained in step 3 is sintered at 1270°C to 1330°C for 2 to 4 hours in a 1 to 2% H2-% N2 reducing atmosphere at a heating rate of 3°C / min and a cooling rate of 4°C / min;

[0037] Step 5: reoxidation; the sample obtained in step 4 is sintered at a temperature of 900-1100°C for 2 hours under the protection of an O2-containing N2 atmosphere (oxygen content of 10-200 ppm) to obtain a final anti-reduction ceramic material. The specific ingredients are shown in Table 1, the specific processes of different embodiments are shown in Table 2, and the performance test results of the obtained material (dielectric loss, dielectric constant, insulation resistivity and capacitance temperature change rate) are shown in Table 3.

[0038] Table 1 Ingredients of Examples 1-10 of Anti-reduction High-performance X7R Ceramic Materials

[0039] Example No. <![CDATA[BaTiO3]]> <![CDATA[MgCO3]]> <![CDATA[SrCO3]]> <![CDATA[Mn3O4]]> <![CDATA[Y2O3]]> <![CDATA[Dy2O3]]> <![CDATA[Ho2O3]]> <![CDATA[Er2O3]]> 1 97.55 0.83 0.98 0.16 — 0.08 0.04 0.35 2 98.71 0.21 0.48 0.04 — 0.33 0.22 — 3 98.32 0.36 0.74 0.13 0.33 — 0.11 — 4 98.81 0.12 0.37 0.12 0.18 — 0.16 0.23 5 98.70 0.60 0.15 0.08 — 0.24 0.23 — 6 98.40 0.44 0.66 0.26 0.24 — — — 7 98.62 0.17 0.82 0.38 — — — — 8 98.13 0.63 0.29 0.42 0.47 — — 0.06 9 99.17 0.28 0.45 0.10 — — — — 10 98.37 0.72 0.61 0.21 — 0.09 — —

[0040] Table 2 Process table of embodiments 1-10 of anti-reduction high performance X7R ceramic material

[0041]

[0042]

[0043] Table 3 Performance of Anti-reduction High-performance X7R Ceramic Material Examples 1-10

[0044]

Claims

1. A high-performance X7R type ceramic material with an anti-reduction property, wherein the dielectric material is mainly made of ultrafine ceramic BaTiO3 with a particle size of 180nm to 230nm, which accounts for 97.40% to 99.10% of the total weight of the dielectric material, and is prepared by adding various secondary additives, including MgCO3, SrCO3, Mn3O4 and one or more oxides of rare earth elements Y, Dy, Ho, and Er, which account for 0.90% to 2.60% of the total weight of the dielectric material.

2. The ceramic material according to claim 1, characterized in that The mass ratio of the materials is: [100-(a+b+c+d)]BaTiO3+aMgCO3+bSrCO3+cMn3O4+dRe2O3, Re2O3 represents a rare earth element oxide. BaTiO3 accounts for 97.40-99.10wt% by mass. The percentage of secondary additives in the total mass of the ceramic material is MgCO3: 0.1-0.9wt%, SrCO3: 0.1-1.0wt%, Mn3O4: 0.1-0.5wt%, Re2O3: 0.1-0.8wt%.

3. A method for preparing a high-performance X7R ceramic material with high reduction resistance, characterized in that: The following steps are involved: Step 1: ball-milling and mixing ultrafine BaTiO3 powder with a particle size of 180nm to 230nm and a modified additive composed of one or more of MgCO3, SrCO3, Mn3O4 and rare earth element oxides Y2O3, Dy2O3, Ho2O3, and Er2O3, and then granulating and molding to obtain a green material; wherein the amount of the modified additive added accounts for 0.90% to 2.60% of the total mass of the barium titanate original powder and the additive; Step 2: sintering: the green body obtained in step 1 is sintered at 1270°C to 1330°C for 2 to 4 hours in a 1 to 2% H2-99 to 98N2 mixed reducing atmosphere at a heating rate of 3°C / min and a cooling rate of 4°C / min; Step 3: Reoxidation: The sample obtained in step 2 is reoxidized for 2 hours at a temperature of 900°C to 1100°C under the protection of an N2 atmosphere containing O2 to obtain a high-performance X7R ceramic material that is resistant to reduction.

4. The method for preparing the anti-reduction high-performance X7R ceramic material according to claim 3, characterized in that: The percentage contents of the secondary additives described in step 1 to the total mass of the ceramic material are MgCO3: 0.1-0.9wt%, SrCO3: 0.0-0.6wt%, Mn3O4: 0.0-0.6wt%, and Re2O3: 0.1-0.8wt%.

5. The method for preparing the anti-reduction high-performance X7R ceramic material according to claim 3 or 4, characterized in that: The ball milling process in step 1 is as follows: deionized water, zirconium balls and powder are mixed in a mass ratio of 2:1:1, the rotation speed is 280 rpm, and the ball milling is performed for 3 to 16 hours.

6. The method for preparing the anti-reduction high-performance X7R type ceramic material according to claim 3 or 4, characterized in that: The granulation process in step 1 is: the ball-milled mixture is dried and mixed with a polyvinyl alcohol aqueous solution and then granulated, and the granulation size is controlled at 80-250 meshes.

7. The method for preparing the anti-reduction high-performance X7R ceramic material according to claim 3 or 4, characterized in that: The molding process described in step 1 is: placing the granulated material into a molding mold and dry-pressing it at a pressure of 12 MPa to obtain a green material.

8. The method for preparing the anti-reduction high-performance X7R ceramic material according to claim 3 or 4, characterized in that: The reoxidation process in step 3 is as follows: the oxygen content in the N2 atmosphere containing O2 is 10-200 ppm and the gas flow rate is 50-70 sccm.

Citation Information

Patent Citations

  • barium titanate-based X8R ceramic material and preparation method and ceramic capacitor thereof

    CN106966719A

  • Anti-reduction X7R type superfine ceramic material and preparation method thereof

    CN117923892A

  • Reduction resistant dielectric composition and ceramic electronic parts using the same

    JP2002338344A